Influence of Rotor Pole Number on the Output of Double Stator Flux-Switching Machine - Awah, Chukwuemeka C.; Nnabuenyi, Ifeanyi K.; Amaghionyeodiwe, Cyril A.; Oti, Stephen E.; Obasi, Ogbonnaya (International Journal of Integrated Engineering, 2023)
Influence of rotor pole numbers on the output performance of a double stator flux-switching permanent magnet machine is investigated and compared in this study. A description of the analyzed machine is first given. Maxwell-2D time-stepping finite element analysis is adopted in estimating the results. The no-load and load characteristics of the investigated machine is considered and quantitatively compared amongst four different rotor pole configurations. The compared machine categories are designated as: 6S/10P, 6S/11P, 6S/13P and 6S/14P, where P stands for rotor pole and S stands for stator slot. It is revealed that the compared 6S/11P machine topology has a lot of good qualities amongst all the compared machine types, since it exhibits the largest electromotive force (EMF), power, torque and greatest overload sustainability feature, etc. Though, the 6S/14P has excellent flux-weakening capability. Moreover, the 6S/13P machine configuration would produce the largest torque if all the compared machines are equipped with same amount of permanent magnet volume/material. The compared machine topologies have reasonably good anti-demagnetization potentials; particularly, the 6S/13P topology.